Eleven minutes - Coelho, Paulo; Costa, Margaret Jull (New York : Harper, 2004)
The story of Maria, a young Brazilian woman who travels to Europe in search of adventure and independence, but finds herself working as a prostitute. Through her relationships and personal reflections, she begins a journey of emotional and spiritual discovery, exploring the nature of love, passion, and inner freedom.
Originally published in Portuguese. Translated from the Portuguese by Margaret Jull Costa.
Keywords: Prostitutes -- Fiction; Love -- Fiction; Self-actualization (Psychology) -- Fiction